2021
DOI: 10.1111/jnc.15380
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical substrates linked to impulsive and compulsive phenotypes in addiction: A preclinical perspective

Abstract: Drug compulsion manifests in some but not all individuals and implicates multifaceted processes including failures in top‐down cognitive control as drivers for the hazardous pursuit of drug use in some individuals. As a closely related construct, impulsivity encompasses rash or risky behaviour without foresight and underlies most forms of drug taking behaviour, including drug use during adverse emotional states (i.e., negative urgency). While impulsive behavioural dimensions emerge from drug‐induced brain plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 211 publications
(238 reference statements)
0
6
0
Order By: Relevance
“…Both pro-inflammatory cytokines and serotonin (5-HT) have been implicated in the aetiology of psychiatric disorders. Impulsivity, as most studies reported, is related to lower forebrain 5-HT transmission, altered 5-HT receptor subtypes ratio, and abnormal serotonergic neural signaling to the mPFC and OFC [45]. As mentioned, elevated pro-inflammatory cytokines are associated with impulsivity.…”
Section: Cytokine-serotonergic Interactionmentioning
confidence: 85%
See 2 more Smart Citations
“…Both pro-inflammatory cytokines and serotonin (5-HT) have been implicated in the aetiology of psychiatric disorders. Impulsivity, as most studies reported, is related to lower forebrain 5-HT transmission, altered 5-HT receptor subtypes ratio, and abnormal serotonergic neural signaling to the mPFC and OFC [45]. As mentioned, elevated pro-inflammatory cytokines are associated with impulsivity.…”
Section: Cytokine-serotonergic Interactionmentioning
confidence: 85%
“…Elevated pro-inflammatory cytokines could disrupt neurotransmission, related to abnormal impulsivity traits, from any one of the three main aspects: synthesis, reuptake, and release of neurotransmitters [44]. The monoamine systems, including serotonin (5-HT), dopamine (DA), noradrenaline (NA), and non-monoamine neurotransmitters such as glutamate and GABA, are critical biochemical substrates of the impulsivity [45]. 5-HT has been implicated in the inhibition of behaviors, and its depletion has various impacts on different forms of impulsivity.…”
Section: Pro-inflammatory Cytokines and Neurotransmitters Involved In...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the behavioral difference between DRL and 5-CSRTT, the neurobiological or psychopharmacological mechanisms of impulsive action evaluated by these two tasks have been considered to be dissociable (D' Amour-Horvat & Leyton, 2014;Jentsch et al, 2014). Despite this, to date, extensive evidence has been largely derived from previous studies using the 5-CSRTT and various kinds of neural or pharmacological manipulations therein (Dalley & Robbins, 2017;Dalley et al, 2008;Jones et al, 2021;Robbins, 2002). In contrast, much less evidence is accumulated from using the DRL task.…”
Section: Drl Task As a Measure Of Impulse Controlmentioning
confidence: 99%
“…Accumulative evidence suggests that maladaptive impulsivity is a behavioral trait that is prominent in various psychiatric disorders, including ADHD and drug addiction (Jentsch et al, 2014;Jones et al, 2021). In the domain of impulsive action, individual differences measured by 5-CSRTT have been shown to be linked to variations in drug addiction behavior in rats (e.g., Dalley et al, 2007;Diergaarde et al, 2008).…”
Section: Future Directions and Potentials Of Using The Drl Taskmentioning
confidence: 99%